Diagnóstico y mejora integral para la empresa “Medical Innovation & Technology S.A.C. - Campos Armijo, María Fernanda (2018)
Medical I&T is a company dedicated to providing technological solutions to its clients, focused on medical software. We analyzed the global and the competitive segment of the company using PESTEL tool and the 5 Porter forces tool, respectively. Finally, we determined that both segments are attractive for Medical’s development.